2010
DOI: 10.1016/j.jaci.2010.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and infant acetaminophen exposure, antioxidant gene polymorphisms, and childhood asthma

Abstract: Background-Prenatal and infant acetaminophen exposure has been associated with an increased risk of childhood asthma phenotypes. Demonstration of biologically plausible interactions between these exposures and maternal and child antioxidant gene polymorphisms would strengthen causal inference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 39 publications
5
95
0
1
Order By: Relevance
“…That said, we cannot rule out the possibility that acetaminophen use in infancy might promote persistence of infant wheezing, and there are clues to suggest that it might influence the developing immune system. In ALSPAC, 35 and two other birth cohorts, 33,37 infant acetaminophen use was associated with an increased risk of childhood atopy. Also, there is the intriguing observation from a randomised trial that prophylactic use of acetaminophen perivaccination was associated with impaired vaccine responses.…”
Section: Acetaminophen In Children and Asthmamentioning
confidence: 90%
See 1 more Smart Citation
“…That said, we cannot rule out the possibility that acetaminophen use in infancy might promote persistence of infant wheezing, and there are clues to suggest that it might influence the developing immune system. In ALSPAC, 35 and two other birth cohorts, 33,37 infant acetaminophen use was associated with an increased risk of childhood atopy. Also, there is the intriguing observation from a randomised trial that prophylactic use of acetaminophen perivaccination was associated with impaired vaccine responses.…”
Section: Acetaminophen In Children and Asthmamentioning
confidence: 90%
“…In keeping with these observations, in the Avon Longitudinal Study of Parents and Children (ALSPAC), a population-based UK birth cohort, we found that the association between infant acetaminophen use and childhood asthma was only seen in individuals who had wheezed in infancy. 35 There are potential difficulties encountered in relying on parental reports of medication use in infancy. These include misclassification of exposure, recall bias, and limited ability to consider dose-response relationships.…”
Section: Acetaminophen In Children and Asthmamentioning
confidence: 99%
“…This study did not confirm a positive association between infant acetaminophen use and atopy reported previously. 7 What should we conclude from these rather mixed findings on infant antipyretic use and asthma? The balance of evidence would appear to be split regarding whether the link between infant acetaminophen use and asthma is confounded by infection, although the possibility of residual confounding cannot be ruled out.…”
mentioning
confidence: 99%
“…In addition, demonstration of plausible interactions between prenatal exposure and maternal antioxidant gene polymorphisms on asthma risk has strengthened causal inference. 7 Of note, acetaminophen use in pregnancy has recently been under the spotlight for reasons other than asthma. For example, birth cohort studies in Norway and Denmark have also reported associations with childhood neurodevelopmental outcomes 9 and behavioral disorders.…”
mentioning
confidence: 99%
“…18 studies recorded lung function as FEV1 % predicted and, as such, enabled comparison between the papers in relation to specific risk factors. In the other 14 papers, six recorded data as raw FEV1 values [16], two used logistic regression to derive FEV1 zscores [17], five used indices other than FEV1 and one recorded observed to expected lung function [18]. We therefore could not include the lung function data from these studies in our analysis in the form in which they were published.…”
Section: Lung Function Measurement: the Challengesmentioning
confidence: 99%